2021
DOI: 10.3390/vetsci8090198
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Water Extract of Fructus Ligustri Lucidi against Oxidative Stress-Related Osteoporosis In Vivo and In Vitro

Abstract: Fructus Ligustri Lucidi (FLL) is the fruit of Ligustrum lucidum Ait and is a component of many kidney-tonifying traditional Chinese medicine formulae for treating osteoporosis. Accumulating evidence has linked oxidative stress with the progression of bone diseases. The present study aimed to identify the effects of FLL on oxidative stress-related osteoporosis in vivo and in vitro. To construct animal models, we utilized d-galactose (D-gal) injection to induce oxidative stress combined with a low calcium (the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…ZL201410037992.5). Pharmacological studies show that EF, LLF, and their active ingredients (such as icariin and baohuoside I in EF and oleanolic acid and ursolic acid in LLF) have anti-OP effects through improving bone microstructure, increasing bone mineral density, and promoting the differentiation and proliferation of OBs [9][10][11][12]. The water extract of LLF can upregulate ERα expression of femurs and tibias of ovariectomy-(OVX-) induced OP rats [13]; EF has the estrogen-like effect which is one of the most important mechanisms of EF in treating OP [14].…”
Section: Introductionmentioning
confidence: 99%
“…ZL201410037992.5). Pharmacological studies show that EF, LLF, and their active ingredients (such as icariin and baohuoside I in EF and oleanolic acid and ursolic acid in LLF) have anti-OP effects through improving bone microstructure, increasing bone mineral density, and promoting the differentiation and proliferation of OBs [9][10][11][12]. The water extract of LLF can upregulate ERα expression of femurs and tibias of ovariectomy-(OVX-) induced OP rats [13]; EF has the estrogen-like effect which is one of the most important mechanisms of EF in treating OP [14].…”
Section: Introductionmentioning
confidence: 99%
“…To validate the therapeutic effects, in vivo studies were carried out in this work. The bone index and bone dry–wet ratio partially reflected the bone quality of mice . Compared with the control group, the dry–wet ratio of femur and humerus in the model group was significantly decreased (Figure B, P < 0.01).…”
Section: Resultsmentioning
confidence: 90%
“…The experimental validation in this study utilized d -galactose-induced oxidative stress combined with a low-calcium diet to construct an animal model of low-conversion osteoporosis . As shown in micro-CT images, OA significantly alleviated osteoporosis in mice in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological studies have reported that FLL can promote differentiation of osteoblasts ( 16 ), inhibit osteoclastogenesis ( 17 ), regulate estrogen levels ( 18 ), and regulate BMD and bone properties via certain pathways, such as the Wnt/β-catenin ( 19 ), NADPH oxidase 4/ROS/NF-κB ( 20 ) and TGF-β1/Smads signaling pathways ( 21 ). Furthermore, FLL also inhibits oxidative stress ( 22 , 23 ) and FLL has been reported to be associated with iron overload ( 24 ). The nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) signaling pathway is an important pathway against oxidative stress and regulates iron and lipid metabolism ( 25 ).…”
Section: Introductionmentioning
confidence: 99%